Technological aspects of the organization of educational practice of future geography teachers in the classical university - Borisenko, K. B. (Problems of Engineer-Pedagogical Education, 2018)
The article analyzes the problem of the formation of special competencies of future geography teachers in the process of educational internship and discloses the technological aspects of internship in the classical university. The stages of the educational practice are considered on the basis of the example of the Department of Physical Geography and Cartography of the Faculty of Geology, Geography, Recreation and Tourism of V. N. Karazin Kharkiv National University. The work provides a detailed analysis of scientific sources on the research problems, highlights the procedural aspects of special competencies formation, analyzes the essence of some concepts, their structural components, and expounds the stages of profession-oriented practice as typical for the classical university. It is noted that today there is a limited number of works, where this problem is considered from the perspective of the competence approach. The paper suggests specific study routes developed by the author, the implementation of which allows the effective development of certain special competencies, the list of which is provided in the text.